Pengaruh Financial Literacy dan Persepsi Risiko Terhadap Minat Berinvestasi Generasi Z di Malang Raya: Perbandingan Antara Minat Investasi di Pasar Modal dan Investasi Emas - Nuzumi, Aminah; Sudaryanti, Dwiyani; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2025)
This research is motivated by Generation Z high spending tendencies and consumerist lifestyle, which makes it difficult to minimize expenses and save. Therefore, managing wealth and financial resources requires adequate skills and knowledge. Investing is a method of financial and wealth management that individual can implement. Lack of financial literacy and high-risk perception are often the main barriers affecting their interest in investing. Therefore, this study aims to analyze the influence of financial literacy and risk perception on investment interest in these two instruments. A quantitative research approach was employed, using Purposive Sampling to select respondents aged 17-26 years from Malang Raya, resulting in 65 participants. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results indicate that financial literacy has a positive and significant effect on investment interest in both the capital market and gold. This means that the higher an individual's financial literacy, the greater the likelihood of their interest in investing. However, risk perception has a significant negative impact on investment interest in gold, while its effect on the capital market is not significant. This suggests that although financial literacy encourages investment interest, concerns about risk can hinder investment decisions, especially regarding gold. Further comparative tests reveal that Generation Z shows a greater interest in investing in gold compared to the capital market. This phenomenon may be related to the perception of gold investment as safer or easier to understand.Keywords: Financial literacy; investment interest; risk perception; generation z.